A role of multiple stakeholder towards sustainable tourism in Setiu wetlands - Mohd Nizam Lani, Zaleha Mohamad, Khyrizan Abu Jalil,; Mohamed Syawal M. Muslim, Wan Izatul Asma Wan Talaat, (Opción, 2019)
This study investigated how stakeholders undertake their responsibilities in developing tourist destination towards sustainable concept in Setiu Wetland. The approach of this study was a quantitative method which involved 120 respondents. The respondents of this study come from domestic and international tourists. The results of the study show all stakeholders played a role as a stakeholder rightly in order to achieve sustainable tourism. In conclusion, each stakeholder should carry out its role and support the policies that have been planned by the Government in order for all the planning in the right base.